MEASURING THE COMPETENCE AND MORALITY OF VILLAGE APPARATUSES IN MINIMISING THE OCCURRENCE OF FRAUD IN VILLAGE FUND FINANCIAL MANAGEMENT - Khoirul Fuad; Farah Aida Ahmad Nadzri; Sharina Tajul Urus; Winarsih; Retno Tri Handayani (International Journal of Accounting, Finance and Business, 2023)
Village funds are special budget allocations that are disbursed by the central government to local governments, in this case revised for villages, every year village fund allocations are received by the village government, and the amount reaches billions of rupiah, along with a large amounts of this allocation, many acts of fraud occur in managing funds. In this village, even ICW (Indonesia Corruption Watch) in 2022 released that most fraud cases, such as corruption, happened in the village fund sector. The population of this study were several village apparatus in Pati Regency, Central Java, who received village fund allocations, while the sampling technique in this study used the convenience sampling method, in addition to the test equipment used in data processing using SEM-PLS. The results showed that the first variable, namely the competence of the village apparatus towards fraudulent village financial management, found negative and insignificant results, while the second variable, namely the morality of the village apparatus, showed a significant negative effect on village financial management.